2023
DOI: 10.1111/ajd.13975
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dynamic dermoscopic features of melanoma and benign naevi by sequential digital dermoscopic imaging and total body photography in a high‐risk Australian cohort

Abstract: Background/Objectives Sequential digital dermoscopic imaging (SDDI) and total body photography (TBP) are recommended as a two‐step surveillance method for individuals at high‐risk of developing cutaneous melanoma. Dermoscopic features specific to melanoma have been well described, however, dynamic changes on serial imaging are less understood. This study aims to identify and compare dermoscopic features in developing melanomas and benign naevi that underwent SDDI and TBP to understand which dermoscopic feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Despite the associated biases, studies based on patient’s recall of first tumour appearance and subsequent changes until diagnosis have shown that some CMMs –generally with atypical clinical features– may become thick lesions in a few weeks, while others grow over years or decades. 29,30 Large multicentre follow-up studies of patients with borderline lesions using sequential digital dermoscopic imaging 31 might offer the opportunity to assess whether the growth rate of excised CMMs can be considered an inverse indicator of the level of diagnostic scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the associated biases, studies based on patient’s recall of first tumour appearance and subsequent changes until diagnosis have shown that some CMMs –generally with atypical clinical features– may become thick lesions in a few weeks, while others grow over years or decades. 29,30 Large multicentre follow-up studies of patients with borderline lesions using sequential digital dermoscopic imaging 31 might offer the opportunity to assess whether the growth rate of excised CMMs can be considered an inverse indicator of the level of diagnostic scrutiny.…”
Section: Discussionmentioning
confidence: 99%